Intensity and Impact of the New York Railroad Superstorm of May 1921. Issue 8 (22nd August 2019) - Love, Jeffrey J.; Hayakawa, Hisashi; Cliver, Edward W.
Abstract: Analysis is made of low‐latitude ground‐based magnetometer data recording the magnetic superstorm of May 1921. By inference, the storm was driven by a series of interplanetary coronal mass ejections, one of which produced a maximum pressure on the magnetopause of 64.5 nPa, sufficient to compress the subsolar magnetopause radius to 5.3 Earth radii. Over the course of the storm, low‐latitude geomagnetic disturbance exhibited extreme local time (longitude) asymmetry that can be attributed to substorm disturbance extending to low latitudes. The storm attained an estimated maximum − Dst on 15 May of 907 ± 132 nT, an intensity comparable to that of the Carrington event of 1859. The May 1921 storm brought spectacular aurorae to the nighttime sky. It also interfered with and damaged telephone and telegraph systems associated with railroad systems in New York City and State. These later effects were due to a combination of three factors: the localized details of geomagnetic vector disturbance, the geographic expression of the Earth's surface impedance tensor, and the configurations and physical parameters of the electrical networks of the day. Plain Language Summary: Historical records of ground‐level geomagnetic disturbance are analyzed for the magnetic superstorm of May 1921. This storm was almost certainly driven by a series of interplanetary coronal mass ejections of plasma from an active region on the Sun. The May 1921 storm was one of the most intense ever recorded by ground‐level magnetometers. It exhibited violent levels of geomagnetic disturbance, caused widespread interference to telephone and telegraph systems in New York City and State, and brought spectacular aurorae to the nighttime sky. Results inform modern projects for assessing and mitigating the effects of magnetic storms that might occur in the future. Key Points: The magnetic storm of May 1921 attained a maximum − Dst of 907 ± 132 nT Low‐latitude geomagnetic disturbance exhibited extreme local time asymmetry Anecdotal evidence from impacts across New York State underscores importance of recent research on geomagnetically induced currents